Improving polio vaccination during supplementary campaigns at areas of mass transit in India - Bahl Sunil; Khaparde Sunil D; Jain Vibhour; Talyan Ashok; Shah Naman K; Hutin Yvan; Wenger Jay (BMC, 2010)
Abstract Background In India, children who are traveling during mass immunization campaigns for polio represent a substantial component of the total target population. These children are not easily accessible to health workers and may thus not receive vaccine. Vaccination activities at mass transit sites (such as major intersections, bus depots and train stations), can increase the proportion of children vaccinated but the effectiveness of these activities, and factors associated with their success, have not been rigorously evaluated. Methods We assessed data from polio vaccination activities in Jyotiba Phule Nagar district, Uttar Pradesh, India, conducted in June 2006. We used trends in the vaccination results from the June activities to plan the timing, locations, and human resource requirements for transit vaccination activities in two out of the seven blocks in the district for the July 2006 supplementary immunization activity (SIA). In July, similar data was collected and for the first time vaccination teams also recorded the proportion of children encountered each day who were vaccinated (a new monitoring system). Results In June, out of the 360,937 total children vaccinated, 34,643 (9.6%) received vaccinations at mass transit sites. In the July SIA, after implementation of a number of changes based on the June monitoring data, 36,475 children were vaccinated at transit sites (a 5.3% increase). Transit site vaccinations in July increased in the two intervention blocks from 18,194 to 21,588 (18.7%) and decreased from 16,449 to 14,887 (9.5%) in the five other blocks. The new monitoring system showed the proportion of unvaccinated children at street intersection transit sites in the July campaign decreased from 24% (1,784/7,405) at the start of the campaign to 3% (143/5,057) by the end of the SIA, consistent with findings from the more labor-intensive post-vaccination coverage surveys routinely performed by the program. Conclusions Analysis of vaccination data from transit sites can inform program management changes leading to improved outcomes in polio immunization campaigns. The number of vaccinated children encountered should be routinely recorded by transit teams and may provide a useful, inexpensive alternative mechanism to assess program coverage.